PENERAPAN SAPTA PESONA TERHADAP PENGELOLAAN LINGKUNGAN PADA DESTINASI WISATA ULEM-ULEM DUSUN ORONG GERISAK DESA TETEBATU KECAMATAN SIKUR KABUPATEN LOMBOK TMUR - Lalu Asnan Kurnia Al Hadi; Siluh Putu Damayanti; Lalu Masyhudi (Journal Of Responsible Tourism, 2023)
This study discusses the application of Sapta Pesona to Environmental Management at Ulem-Ulem Tourism Destinations, Orong Gerisak, Tetebatu Village, Sikur District, East Lombok Regency. This research was conducted to answer the problems how to apply Sapta Pesona in improving environmental management, what are the obstacles in implementing Sapta Pesona and the efforts made to improve the application of Sapta Pesona to environmental management in Ulem-Ulem tourist destinations. The research method used is a qualitative method with data collection techniques, namely interviews, observation and documentation. The results of this study indicate that the application of Sapta Pesona in the tourist destination of Ulem-Ulem is not good. Sapta pesona directly impacts the environment when applied, where if Sapta pesona is applied the environment will be more well-groomed and comfortable to visit while if Sapta pesona has not been applied it will cause the environment to become less well-maintained, less comfortable and even to the point of damaging the environment. The obstacle faced in implementing Sapta Pesona in the tourist destination of Ulem-Ulem is the problem of funds. The problem of Sapta Pesona related to environmental management in Ulem-Ulem tourist destinations is the problem of cleanliness, order and hospitality, efforts that can be made to improve the application of these elements are: for the clean element by holding mutual cooperation to clean tourist destinations, to the orderly element by enforcing strict disciplinary regulations and for the friendly element by conducting socialization and training.